The pragmatic liberalism of public administration - Miller, Hugh T. (2004)
The intellectual growth and development of the field of public administration can be caracterized as an enduring, grand conversation. The discourse among the community of scholars in public administration is an ongoing one, yet the plurality of paradigms and perspectives seems overwhelming at times. We have not gotten it right yet, and if the contestability of the discipline's foundations, prescriptions, truths and realities continues as the central feature of the field's discourse, we never will get it right. This would be a good thing. - Reproduced.
Keywords: Pragmatism; Liberalism; Public administration